Therapeutic Effect and Cost-Benefit Analysis of Three Different Nutritional Schemes for Esophageal Cancer Patients in the Early Post-operative Period - Huang, Chen; Liang, Xinyu; Du, Shanshan; He, Jie; Bai, Qian; Feng, Xiaoqing; Liu, Xiaoqing; Tian, Xu; Wang, Jian (Frontiers in Nutrition, 2021)
Objective: To retrospectively investigate the comparative efficacy, safety and cost-benefits of three nutritional treatment schemes including short peptide jejunal nutrition (SPJN), whole protein jejunal nutrition (WPJN), and partial parenteral nutrition (PPN) in patients underwent esophagectomy for esophageal cancer in our hospital. This study was carried out in accordance with the conceptual framework of nutritional therapy in fast-track rehabilitation surgery. Methods: We retrospectively reviewed 305 patients who were assigned to receive esophagectomy for esophageal cancer. Eligible patients was naturally divided into SPJN group [n = 98 (32.1%)], WPJN group [n = 95 (31.1%)], and PPN group [n = 112 (36.7%)] according to the type of nutritional scheme which was actually prescribed to patients by the attendingphysician in clinical practice. The differences of the serum total protein (TP), albumin (ALB), pre-albumin (PA), hemoglobin (HGB), white blood cells (WBCs), red blood cells (RBCs) and neutrophils were compared among 3 nutritional schemes groups. We also investigated the relationship of the fluid intake, urine output, gastric juice drainage volume and thoracic drainage volume among 3 nutritional groups at 3 days after surgery. Moreover, the differences of cost-benefit indexes, complications, length of hospitalization and hospital expenditure were also compared. Results: The serum TP, ALB, and PA in the SPJN group were all higher than those in the WPJN and PPN groups (p < 0.05). The gastric juice volume of gastrointestinal decompression drainage and fluid volume of thoracic drainage in the SPJN group were all less than that in the WPJN group (p < 0.05). The overall hospital stay and post-operative hospital stay in the SPJN group were all shorter than that in WPJN group (p < 0.05). Moreover, the incidence of post-operative complications including anastomotic leakage, infection, and gastrointestinal reaction was remarkably lower in the SPJN group compared to the WPJN group (p < 0.05). Interesting, hospital expenditure in the PPN group was less than that in the SPJN and the WPJN groups (p < 0.001). Conclusion: Patients may obtain benefits in improving protein level after receiving SPJN scheme at the early stage after esophagectomy. Meanwhile, patients may obtain benefits in improving post-operative complications and hospital stay after receiving SPJN or PPN compared to WPJN protocol. However, the difference between SPJN and PPN requires further study because no difference was detected in terms of clinical outcomes including complications and the length of hospitalization although PPN may achieve a possible decrease of medical expenditure.